Studi Pranata Islam ( Politik, Ekonomi, dan Hukum) - Qomariyah, Putri; Rizqa, Choirus Syifaul (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
The study of Islamic institutions is the study of Islamic procedures affecting all fields concerned with human beings, such as political, economic, and legal aspects. This study covers in terms of religion and all aspects of human life from politics, economics, and law. The study of political Islam discusses how Islamic teachings can be applied in the political system and can influence the political decision-making process. The study of Islamic economics deals with the principles of Islamic economics and how principles such as politics, economics and law can be applied in everyday life. While the study of Islamic law discusses the Islamic legal system and how the teachings of Islam can be applied in various aspects of law, such as civil law, Family Law, and criminal law. In writing this journal article formulates how the differences in political, legal, economic development of Islamic civilization and in the state of Indonesia. The type of method used in this writing is using qualitative descriptive method using library research or with library research, where the data used is Library data. Primary Data used in this writing are journals and books related to the history of Islamic civilization and the state of Indonesia by collecting various information that is considered relevant and in accordance with the problems studied in this writing. The results of this study are political, economic, and legal aspects in Indonesia that continue to develop following the flow of modern times that remain guided by Islamic institutions and do not eliminate the characteristics of a democracy with the motto Unity in diversity.